The Abū Ṣalābīkh Tablets. A Preliminary Survey (The Literary Texts – The Lexical Texts – The Exercise Tablets – The Economic Texts) - Biggs, Robert D.
78: AbS T 393; 79: AbS T 44a-f (copies); 83: AbST 222 rev. (photo); 85. 87: AbST 80; 86: AbS T 14 (photo; transliteration: 87-88).